ANTECEDENTS OF EMPLOYEE ENGAGEMENT AND ITS IMPACT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN LECTURER IN POLITEKNIK NEGERI LHOKSEUMAWE - Zahratul Dahlia; Marbawi; Yanita; A Hadi Arifin; Mohd. Heikal; Em Yusuf Iis (RADJA PUBLIKA, 2023)
The purpose of this study is to determine and analyze the effect of transformational leadership and organization culture on organizational citizenship behaviour with employee engagement as a mediating variable. The number of respondents in this study are 172 lectures in Politeknik Negeri Lhokseumawe. Data analysis method used is Structural Equation Modeling by using AMOS software. The results of this study found that directly, transformational leadership and organization culture have a positive and significant effect on employee engagement, then organization culture and employee engagement also have positive and significant effects on organizational citizenship behaviour, but transformational leadership has no significant effect on organizational citizenship behaviour. The mediation effect test results proved that employee engagement mediates the influence of organizational culture on organizational citizenship behaviour partially (patial mediation), but employee engagement cannot mediate the effect of transformational leadership on organizational citizenship behaviour.